Urgensi Modul Ajar Pada Kurikulum Merdeka Dalam Pembelajaran Bahasa Arab di Madrasah Ibtidaiah (MI) - Siagian, Amalia Alfina; S, Sapri; Kesuma, Bunga; Pratiwi, Eyzi; Rangkuti, Khairina Habib; K, Khairunnisa; Labib, M. Dzaky; Putri, Nindya (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The development of teaching modules in Arabic language learning at Madrasah Ibtidaiah (MI) is the main focus in supporting the independent curriculum in Indonesia. Teaching modules provide a consistent framework for teachers to design learning that suits student needs, encourages interactive learning, and creates an inclusive environment. The research method used is descriptive qualitative with a semiotic analysis approach, emphasizing in-depth understanding of individuals and symbols in the text. Data was obtained from literature studies, journals, books and scientific works. The research results show that teaching modules play an important role in maintaining consistency of learning, enabling the integration of religious knowledge and Arabic, and facilitating the use of technology in learning. Apart from that, the teaching module also increases the efficiency of learning time by preparing an integrated guide with the Learning Implementation Plan (RPP). This helps teachers deliver material in a planned and efficient manner. The importance of teaching modules is also reflected in their ability to adapt learning to student needs. Teachers can adapt materials, methods, media and learning speed according to students' levels, interests and abilities. Thus, teaching modules become a crucial element in supporting an independent curriculum in learning Arabic at MI. This research highlights the urgency of developing teaching modules that are relevant, effective, and able to support students' individual needs in order to create a more efficient and inclusive learning process.